Peran e-Government dalam Penerapan Protokol Kesehatan di Puskesmas dan Rumah Sakit di Kota Surabaya - Lira Yuanita; Afidatul Asmar (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2022)
The existence of a new variant of the Delta type of COVID-19 virus has caused an explosion of positive cases in Indonesia. The explosion of positive cases was accompanied by the development of information technology, one of which was e-Government. Based on Presidential Instruction number 3 of 2003, the President appealed to each regional head to develop e-Government in their respective work environments. Surabaya is one of the cities that has developed e-Government since 2002. Nationally, the city of Surabaya is recognized as having a good e-Government system. One of the e-Governments developed by the City of Surabaya is e-Health. E-Health is one of the applications built by the Surabaya City Government in the health sector. This paper will discuss the role of the e-Health application in the implementation of the Health Protocol in the city of Surabaya. The writing methodology uses a literature review with a semi-systematic review approach. Data were collected from several scientific studies and observation techniques. The results of this study are e-Health applications can create distance between individuals, avoid crowds in public health center and hospital buildings, and reduce mobility and community interaction to queue. This is due to the arrangement of patient service hours. In addition, people who come to health centers and hospitals are also required to wear masks and wash their hands in the places provided. The conclusion obtained from this paper is that the e-Health application strongly supports the application of health protocols in the city of Surabaya. For that It is hoped that other cities in Indonesia will also develop and implement e-Government, so facilitating public services can be implementing health protocols.